Analisis PDRB Subsektor Tanaman Pangan dan Perkebunan Kabupaten/Kota Di Propinsi Jambi dengan Belanja Modal Sebagai Faktor Yang Mempengruhinya - Muhammad Safri; Yoga Prasetya (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to determine the effect of capital expenditure to the Gross Domestic Product (GDP) of Food Corp and Plantation Subsectors of the District / Municipality in Jambi Province. The populations in this study are all districts / municipalities in Jambi Province. The populations in this study are 11 districts / cities, because the population is less than 100, then the entire population were being sampled. The analytical method used in this research is panel data regression. The results of this study indicate that capital expenditure significantly affected to the GDP of Food Corp and Plantation Subsectors of the District / Municipality in Jambi Province.